Payer costs of patients diagnosed with epilepsy. - Griffiths, R; Schrammel, P; Morris, G; Wills, S; Labiner, D; Strauss, M (Lippincott Williams and Wilkins, 1999)
PURPOSE: To identify the annual cost to a third-party payer of inpatient and outpatient services and prescription drugs for patients diagnosed with epilepsy or convulsions. METHODS: Retrospective study using administrative and claims data from a private insurer in the Northeast United States with >1.8 million covered lives. Health plan members were included if they had a claim for epilepsy or convulsions and a claim for an antiepileptic drug (AED) between January 1992 and December 1996. Annual costs and frequencies of all medical services, and of services related to epilepsy, were compared among five groups of patients defined by the most intensive procedure they received: invasive therapeutic procedure (group 1); invasive diagnostic procedure without an invasive therapeutic procedure (group 2); noninvasive diagnostic procedure without an invasive procedure (group 3); neurologist or neurosurgeon visit without an invasive procedure or noninvasive diagnostic procedure (group 4); or none of the preceding services (group 5). RESULTS: In the cohort of 9,090 patients meeting the inclusion criteria, mean age was 38 years, 53% were female, 30% had malignant disease, and 25% had cardiac disease. The mean annual cost of all medical services was $9,617. Mean annual costs of all services were $43,333, $29,847, $11,300, $4,362, and $5,855, and annual costs of inpatient and outpatient encounters coded as epilepsy plus AEDs were $24,369, $10,330, $3,127, $1,079, and $1,086, in groups 1-5, respectively. Services used to stratify patients into the groups accounted for 37% of the total costs. CONCLUSIONS: The annual costs of medical services for patients with epilepsy are high and vary considerably because of treatment of epilepsy and management of comorbidities.